Adrenal Lymphangioma Masquerading as a Catecholamine Producing Tumor - Israel Hodish; Lindsay Schmidt; Andreas G. Moraitis (Case Reports in Endocrinology)
Objective. To report the unusual case of an adrenal lymphangioma presenting in a patient with an adrenal cystic lesion and biochemical testing concerning for pheochromocytoma. The pertinent diagnostic and imaging features of adrenal lymphangiomas are reviewed. Methods. We describe a 59-year-old patient who presented with hyperhidrosis and a 2.2 by 2.2 cm left adrenal nodule. Biochemical evaluation revealed elevated plasma-free normetanephrine, urine normetanephrine, urine vanillylmandelic acid, and urine norepinephrine levels. Elevated plasma norepinephrine levels were not suppressed appropriately with clonidine administration. Results. Given persistent concern for pheochromocytoma, the patient underwent adrenalectomy. The final pathology was consistent with adrenal lymphangioma. Conclusions. Lymphangiomas are benign vascular lesions that can very rarely occur in the adrenal gland. Imaging findings are generally consistent with a cyst but are nonspecific. Excluding malignancy in patients presenting with adrenal cysts can be difficult. Despite its benign nature, the diagnosis of adrenal lymphangioma may ultimately require pathology.